Dynamic Mechanical Properties and Fractal Characteristics of Polypropylene Fiber-Reinforced Cement Soil under Impact Loading - Yi-xin Mo; Jian-yong Pang; Jin-kun Huang (Advances in Materials Science and Engineering)
This paper aims to study the dynamic mechanical properties, failure patterns, fractal behaviors, and energy dissipation of polypropylene fiber-reinforced cement soil under impact loading. Dynamic compression tests for reinforced cement soil with different polypropylene fiber contents of 0%, 0.4%, 0.8%, and 1.2% were conducted using a 50 mm diameter split Hopkinson pressure bar (SHPB) device. The static and dynamic stress-strain curves, dynamic strength increase factor (DIF), fractal behaviors, and energy dissipation properties of polypropylene fiber-reinforced cement soil were investigated and analyzed. The experimental results indicated that the dynamic strength increase factor (DIF) of cement soil increases firstly and then decreases with the increase of polypropylene fiber content from 0% to 1.2%. The maximum dynamic compressive strength of cement soil was obtained with adding 0.8% polypropylene fiber. With the increase of polypropylene fiber content, the average particle size of cement soil fragments has an increasing trend, whereas the fractal dimension presents a decreasing trend. Besides, the fragmentation degree of cement soil decreases correspondingly with the increase of polypropylene fiber content. The fractal dimension value has a linear relationship with the polypropylene fiber content and a decreasing exponential relationship with the average particle size. The absorbed energy per unit volume of cement soil presents an increasing trend firstly and a decreasing trend subsequently as the polypropylene fiber content increases from 0% to 1.2%. When the fractal dimension of cement soil is kept in the range of 2.04 to 2.15, the absorbed energy per unit volume of cement soil increases first and then decreases. The absorbed energy per unit volume of cement soil has a quadratic parabola relationship with polypropylene fiber content and fractal dimension, respectively. At last, the relationship of the absorbed energy per unit volume, fractal dimension, and polypropylene fiber content can be established, which can be used in the studies of dynamic behaviors and fractal properties of the fiber-reinforced cement soil under impact loading.